Metalinguistic knowledge in instructed second language acquisition: A theoretical model and its application in computer-mediated communicationi - O'ROURKE, BREFFNI (University of Dublin, Trinity College, 2003)
This thesis has three interrelated aims: (1) to elaborate a model of instructed second language acquisition (SLA) that brings together insights from cognitive research in second language acquisition and from the developmental and learning theories of Lev Vygotsky; (2) to identify the pedagogical implications of this model; and (3) to evaluate this pedagogy as implemented in a computer-mediated communication (CMC) environment. Chapter 1 critically assesses existing Vygotskian second language research and concludes that much of this research is based on an inadequate understanding of Vygotsky?s theory. More emphasis should be given to the individual-cognitive dimension of Vygotskian theory: the role of consciousness is crucial, providing an important point of interface with mainstream SLA research. Chapter 2 reviews the literature on the role of consciousness in SLA, and especially Schmidt?s noticing hypothesis and Truscott?s critique thereof. Karmiloff-Smith?s model of representational redescription in cognitive development forms the basis of the model of instructed SLA, which incorporates insights from the discussions of Vygotsky and noticing. Metalinguistic knowledge emerges as playing important roles in language use and learning. Chapter 3 draws out the pedagogical implications of the model and suggests that tandem language learning (an exchange involving bilingual learning partnerships) and engagement with written language have important roles to play in any implementation of this pedagogy. It further assesses the benefits that CMC, and specifically a system known as a MOO (Multiple User Domain, Object-Oriented), might bring to such an implementation. Chapters 4 and 5 contain an empirical study of tandem learning in the MOO, based on data from a German-Irish tandem exchange. Chapter 4 sets out the institutional and pedagogical context and analyses preliminary data relating to participation, interaction and language balance. Chapter 5 focuses on the substantive questions of metalinguistic behaviour and processes. MOO session transcripts are analysed under the headings of negotiation of meaning, self-repair, and other-correction, and the success of a prescribed writing/peer-reformulation task in generating metalinguistic dialogue is evaluated. On the basis of online interview data, tentative conclusions are drawn concerning the metacognitive processes that take place in the MOO interaction. The study cannot claim to have shown that interacting in a MOO brings with it automatic benefits in the form of metalinguistic processes. Rather, the evidence leads us to the replacement of a simple causal model of the relationship between communications medium and metalinguistic process with a three-part model of compulsions, affordances and potentials for metalinguistic reflection. This model should be applicable also to other applications of computer technology to language learning. The value of the tandem learning framework is clear, but it is essential to match partners as closely as possible in terms of language proficiency.
PUBLISHED
Keywords: computer-mediated communication; cmc; second language acquisition; sla; Vygotsky; virtual environments; computer-assisted language learning; CALL; tandem language learning; etandem; representational redescription; Karmiloff-Smith; scientific concepts; spontaneous concepts; metalinguistic knowledge; language-related episodes; interactionist hypothesis; negotiation of meaning; metalinguistic discourse; language-related episodes; telecollaboration; International Integration; Smart & Sustainable Planet